Gluten-Free Diet in Children with Dermatologic Pathology - Leonid A. Opryatin; Tatiana E. Borovik; Nikolay N. Murashkin (Педиатрическая фармакология)
Background. Gluten-free diet (GFD) is a nutritional pattern that excludes such component of grain crops as gluten. This diet administration should be strictly regulated due to its influence on the growing child nutritional status and on the course of skin diseases. Thus, studying the effects of GFD on the course of dermatologic diseases in various patients’ groups is crucial.Objective. The aim of the study is to study the effects of GFD on nutritional status and skin condition of patients with dermatologic pathology and associated celiac disease, as well as gluten hypersensitivity.Methods. The study included children hospitalized in the dermatology department. We have used obtained anthropometric data (weight, height, body mass index (BMI)) to estimate nutritional status, all calculations were performed via programs WHO Anthro (for children under 5 years old) and WHO AntroPlus (for children over 5 years old). Weight-for-age (WAZ), height-for-age (HAZ), BMI-for-age (BAZ) z-scores were evaluated. Estimation of skin pathological process was performed via SCORAD index for patients with atopic dermatitis, PASI — for psoriasis, SALT — for alopecia, VASI — for vitiligo, LoSCAT — for scleroderma. Assessment of anthropometric measures and skin disease severity was performed at study initiation and 6 months after nutrition correction.Results. 1000 children with various dermatologic pathologies admitted to the dermatology department during the period from August 2020 to August 2021 were examined. Three patients’ groups were formed: with celiac disease, gluten hypersensitivity, and without any gluten-associated conditions. Assessment of anthropometric measures has shown positive dynamics in patients with celiac disease and gluten hypersensitivity on GFD, as well as in patients without any gluten-associated conditions on normal caloric diet according to age norms. All three groups have shown positive dynamics for skin pathologies.Conclusion. Estimation of nutritional status and skin conditions on various stages of the study has shown the importance of differentiated approach in GFD administration in dermatologic patients.